(untitled) (JONAH : Journal of Nursing and Homecare, 2024)
The application of ergonomic principles in the workplace has not received full attention, especially for nurses in hospitals. There is not much information about the perceptions of nurses in intensive care and the emergency room about ergonomic hazards and their preventive actions. The purpose of this research was to explore experiences and perceptions of nurses in intensive care and emergency room in preventing the ergonomic hazards during the implementation of nursing care. This qualitative study used Focus Group Discussion (FGD) to collect the data from a hospital in Pekanbaru. The participants consisted of 17 nurses who worked in intensive care room and 10 nurses who worked in emergency room. This research used Colaizzi strategies to analyze the data by comparing perceptions of nurses who worked in intensive care and emergency room. The research results showed that both groups had similar understanding on the ergonomic hazards, similar perceptions on the importance of paying more attention to the ergonomic hazards, and similar preventive actions to make. Further, there were similar perceptions on factors influencing the preventive actions to the ergonomic hazards as well as similar expectations and needs in improving the preventive actions toward ergonomic hazards. The participants had similar valuable experiences and ideas which should be considered in improving the preventive actions toward the ergonomic hazards while working in the hospital. Those expectations are in the forms of education, socialization, reminder from other nurses, and supports from the head nurse to improve knowledge, self-awareness, and appropriate preventive actions toward the ergonomic hazards